INVESTIGATION ON FORMULATION VARIABLES FOR PREPARATION OF FLUCONAZOLE-LOADED SPANETHOSOMES - SAHIB, SAJATAHER; SABRI, LUBNA A. (International Journal of Applied Pharmaceutics, 2026)
Objective: This study aimed to develop fluconazole (FLC)-loaded spanethosomes by investigating the effects of various formulation variables, with the goal of identifying the optimal formulation that exhibits desirable vesicular characteristics for topical delivery. Methods: Fifteen formulations containing 0.5% w/v FLC spanethosomes were prepared using the ethanol injection method. The formulations were assessed for vesicle size, polydispersity index (PDI), entrapment efficiency and in vitro drug release. The optimal formulation was further characterized for its morphological features and FTIR spectra. Results: All prepared spanethosomes exhibited nanoscale vesicle sizes ranging between 79±8.54 and 3517±80.85 nm, with entrapment efficiency between 42.35±4.55 and 95.46±0.68%. The optimum formula, composed of Span 60 and sodium deoxycholate (SDC) in a 200:15 mg weight ratio, exhibited a spherical morphology without aggregation. It achieved a cumulative FLC release of 94.6% within 6 h. Conclusion: These results suggest that spanethosomes are promising drug delivery systems that can enhance the therapeutic efficacy of FLC for treating superficial fungal infections while minimizing systemic side effects.